Focus Group Discussion on The Rationality of Using Gastritis Drugs in Patients Suffering from Osteoarthritis at The Batang Kuis Health Center - Syarifuddin, Aminah (JURNAL PENGMAS KESTRA (JPK), 2023)
In developing countries, chronic gastritis is the most common type of gastritis with In various countries currently, chronic gastritis occupies a position as a frequently encountered gastritis disease, where the prevalence depends on geographic and socio-economic conditions. Gastritis is a type of disease that causes inflammation of the stomach mucosa. If you take osteoarthritis medicines such as NSAIDS without instructions for use, it will trigger gastrointestinal disease. Gastritis is one of the types of disease with the highest incidence rate. Age and gender factors are generally very susceptible to gastritis. Osteoarthritis (OA) is a type of arthritis that has chronic impacts and causes many public health problems. Osteoarthritis presents with many different symptoms. The aim of this PkM activity is to educate PkM participants in understanding the gastritis drug regimen that should be recommended to osteoarthritis patients and the rationale for treatment. Seminar activities are carried out using lecture and Focus Group Discussion (FGD) methods. The PkM participants were patients at the Batang Kuis Community Health Center, totaling 50 patients who were determined randomly. There were 30 male patients and 20 female patients. The questionnaire was chosen as a measuring tool to measure the success of this PkM activity. The PkM results showed that 90% or 45 PkM participants stated they were very satisfied with the rationality of using gastritis medication and there were 10% or 5 PkM participants who stated they were satisfied.